Inspiration and insinuation influences on human thinking and behavior: a psychoanalytical, psychodynamic, and cognitive phenomenon - Badi, Jamal Ahmed Bashier; Olorogun, Lukman A. (Canadian Center of Science and Education, 2015)
Is insinuation one of the most influential phenomena in the early and continuous development of human behavior? Yes. Does previous scientific study give ample of time to understand unconsciousness and its manifestation from this point of view? No. As we have demonstrated in the following pages, insinuation does hold a high view in the divine scriptures as an opposite to inspiration. The scientific views on unconsciousness theory further ascertained its influence on human activities. A number of scientists however, denounced this clear evidence due to lack of laboratory prove of inspiration-cum-insinuation effects rather termed unconsciousness. In this essay, through dedicated analysis using both induction and deduction methods we showed that their theories failed to study unconsciousness from a holistic perspective. It only focused on those that have psychological and psychopathological problems in exclusion of reasonable human beings, thus, contained numerous errors that even contradicted their scientific findings. Following in-depth and dedicated analysis, we showed the influences of unseen phenomena that are beyond human control from Islamic philosophy viewpoints affirming earlier biblical claims of insinuation influences. We concluded by mentioning some of the physical evidences justified by the Islamic scripture “Qur’an” and some of the implications of these findings for certain aspects of the contemporary “inspiration and insinuation debates”. Keywords: psychoanalysis, human memory, inspiration and insinuation, cognitive phenomenon, behavior